2003
DOI: 10.1016/s1063-4584(03)00087-6
|View full text |Cite
|
Sign up to set email alerts
|

Motile chondrocytes from newborn calf: migration properties and synthesis of collagen II

Abstract: A population of well-differentiated chondrocytes capable of matrix (COL II) synthesis are motile in vitro. This original finding opens new avenues to study the potential of motile cells for cartilage repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
64
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 43 publications
9
64
1
Order By: Relevance
“…Our results indicate that BSA inhibits chemotaxis of MSCs in the TCA, whether it is used in the cell buffer or in the chemoattractant buffer. We also found that premigration attachment time, employed in some studies with mesenchymal cell types (57,58), significantly reduced cell migration. This may not be surprising because it is well established that optimal migration depends on a fine balance between attachment and detachment from the substrate (25).…”
Section: Transmembrane Chemotactic Assay Optimized By Removal Of Bsa supporting
confidence: 65%
See 1 more Smart Citation
“…Our results indicate that BSA inhibits chemotaxis of MSCs in the TCA, whether it is used in the cell buffer or in the chemoattractant buffer. We also found that premigration attachment time, employed in some studies with mesenchymal cell types (57,58), significantly reduced cell migration. This may not be surprising because it is well established that optimal migration depends on a fine balance between attachment and detachment from the substrate (25).…”
Section: Transmembrane Chemotactic Assay Optimized By Removal Of Bsa supporting
confidence: 65%
“…We initially examined the effect of attachment time used to allow MSCs to settle and adhere to the membrane before establishing a gradient of soluble chemoattractant (57,58). When no premigration cell attachment time was allowed before adding the chemoattractant in the bottom chamber, 20% of all rabbit bone marrow-derived MSCs migrated toward 10 ng/ml PDGF-BB during 4 h (Fig.…”
Section: Optimization Of the Transmembrane Chemotaxis Assaymentioning
confidence: 99%
“…A distinct advantage of the ACI procedure is the utilization of chondrocytes that produce appropriate ECM to replace the cartilage defect. Because chondrocytes have limited motility in vitro, [39][40][41] it is reasonable to assume that the native chondrocytes are unlikely to migrate a significant distance into the implanted biomaterial scaffold. We did not find such cells in the non-cell seeded scaffolds of the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the chemoattractive effects of these growth factors may enhance integration with surrounding tissue by further stimulating chondrocytes to migrate toward the scaffolds. [218][219][220] Hydrogels have long been popular as controlled delivery systems for proteins, because release profiles can be modulated by changing the hydrogel crosslinking density, which changes the free space available for diffusion. 228 The mechanisms of release can also be varied by manipulating interactions between encapsulated proteins and the hydrogel polymer, such as charge interactions, or by changing the degradation profiles of the hydrogels.…”
Section: Controlled Release Of Growth Factorsmentioning
confidence: 99%